Pembinaan Disiplin Kerja Pegawai Di PUPR Balai Wilayah Sungai Sumatera V SNVT Pelaksanaan Jaringan Pemanfaatan Air IAKR - Tania Zemerlin; Irsyad Irsyad; Jasrial Jasrial; Yulianto Santoso (Journal of Educational Administration and Leadership, 2021)
This research was made to obtain information at PUPR Balai Sungai Sumatera V SNVT Implementation of IAKR Water Utilization Network regarding: 1) Leadership Assertiveness, 2) Leadership Model, 3) Supervision Activities, and 4) Sanctions for Violations. The author uses descriptive or quantitative research. The author used a questionnaire in this study with a Likert scale model with a population of all employees at PUPR Balai Sungai Sumatera V SNVT Implementation of the IAKR Water Utilization Network, amounting to 62 employees, the number of samples that researchers used for this study amounted to 38 people taken 10% of the population. The results of what the researchers found at PUPR Balai Sungai Sumatera V SNVT Implementation of IAKR Water Utilization Network are: 1) Assertiveness of leaders with an average number of 3.86 is in good criteria, 2) exemplary leadership with an average number of 4.00 are in good criteria, 3) Supervision activities with an average number of 3.78 are in good criteria, and 4) Sanctions for violations with an average number of 4.05 are in good criteria. Overall, it can be seen that the level of employee work discipline development at PUPR Balai Sungai Sumatera V SNVT Implementation of IAKR Water Utilization Network with an average number of 3.92 on good criteria.